Penerapan Metode Belajar Sambil Bermain Dalam Mengembangkan Minat Belajar Anak-Anak Gang Perwira Medan - Shifa Bilbi; Mia Aulina (Yayasan Literasi Sains Indonesia, 2022)
Interest is a sense of preference, interest, attention, focus, persistence, effort, and the result of a person's or individual's interaction with certain content or activities. One of them is learning while playing to foster one's interest in learning, seeing children's playing spirit is very high, therefore it is combined so that learning is not left behind. Children get bored quickly if it is not combined with methods like this, in addition to increasing interest in learning, it also increases creativity for the officers of Gang officers. The process of helping to increase interest in learning with the PKL I mini project using the casework method through the individual intervention stages of Engagment Intake Contract, Assessment, Planning / Planning, Intervention, Evaluation, and Termination. The focus of the client problem solving process is the use of the Learning While Playing method as a jointly designed strategy to increase the client's interest in learning. The purpose of this program is stated to have been achieved, proven, and an increase in the enthusiasm for learning and a great curiosity towards mathematics and other sciences